Marylan Lawrence. - (:unkn) unknown (Forsyth County Public Library, 2009)
Photo was made in the 1960s.
Marylan Lawrence.
Keywords: Forsyth County (N.C.) -- History -- Pictorial works; Forsyth County (N.C.) -- History -- Sources; Digital Forsyth